Blue Economy and Regional Economic Growth: Evidence from the Competitiveness of Local Marine Products in Simeulue Regency, Indonesia - rita handayani; Hastina Febriaty; EE Danil (CERED Indonesia Institute, 2026)
This study aims to analyze the role of the local marine product sector as a driver of economic growth in Simeulue Regency and formulate a direction for sustainable Blue Economy development. The study uses a quantitative approach with the Location Quotient (LQ) method to identify base sectors and Shift-Share to analyze the competitiveness and growth dynamics of the marine sector during the 2013–2023 period. The results show that the marine sector is the engine of economic growth in Simeulue Regency. The LQ analysis shows that aquaculture is a base sector that has a significant contribution to the regional economy, while the Shift-Share analysis shows that capture fisheries have a higher competitive advantage than the average in Aceh Province. However, the aquaculture sector still requires technological modernization to improve regional competitiveness. Policy implications emphasize the importance of strengthening the Blue Economy through increased investment in aquaculture technology, development of a circular bioeconomy, coastal ecosystem conservation through a blue carbon strategy, increasing human resource capacity, and implementing a Social License to Operate to strengthen community participation. Synergy between economic growth, social inclusion, and environmental sustainability is a key prerequisite for increasing the added value of the marine sector, creating jobs, and encouraging inclusive and sustainable regional economic growth